Differential effects of stress exposure via two types of restraint apparatuses on behavior and plasma corticosterone level in inbred male BALB/cAJcl mice - Hirotaka Shoji; Tsuyoshi Miyakawa (Wiley, 2020)
Abstract Aims Restraint stress is one of the most widely used experimental methods for generating rodent models of stress‐induced neuropsychiatric disorders, such as depression and anxiety. Although various types of restraint apparatuses have been used to expose animals to stress, the magnitudes of the effects of stress exposure via different types of restraint apparatuses on physiology and behavior have not been compared in the same environment. Here, we investigated the effects of stress exposure via two types of restraint apparatuses on body weight, locomotor activity, anxiety‐ and depression‐related behaviors, and plasma corticosterone levels in mice. Methods Adult male BALB/cAJcl mice were restrained by placing them in either a well‐ventilated plastic conical tube or a tapered plastic film envelope for 6 hours per day for 10 or 21 consecutive days. Mice were weighed during and after the stress period and were subjected to a battery of behavioral tests, including light/dark transition, open field, elevated plus maze, Porsolt forced swim, tail suspension, and sucrose preference tests, starting on the day after the last stress session. Plasma corticosterone levels were measured in another cohort of mice on the 1st and the 21st stress sessions and after the Porsolt forced swim test. Results Exposure to repeated stress via the two above mentioned types of restraint apparatuses caused body weight loss, heightened locomotor activity, altered immobility during forced swim, and increased plasma corticosterone levels, and some of these results differed between the restraint stress protocols. Film‐restraint-stressed mice had significantly lower body weights than tube‐restraint-stressed mice. Film‐restraint-stressed mice exhibited significantly higher or lower immobility during forced swim than tube‐restraint-stressed mice, depending on the test time. Additionally, the stress‐induced increase in plasma corticosterone levels was found to be higher in film‐restraint-stressed mice than in tube‐restraint-stressed mice. Conclusion Our results indicate that film‐restraint stress has more pronounced effects on body weight, depression‐related behavior, and corticosterone response than tube‐restraint stress in mice. These findings may help guide which restraint stress procedures to use, depending on the objectives of a given study, in generating animal models of stress‐induced neuropsychiatric disorders.